Pengaruh Kepercayaan, Keamanan Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Di Shopee (Studi kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Ahmad Naufal; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of trust, security and service quality on purchasing decisions, the sample of this research is the Shoppe site consumers. Data collection using questionnaires, data analysis using validity tests, reliability tests, normality tests, multiple linear analysis, F statistical tests and t statistical tests, testing the coefficient of determination on the IBM Social Sciences Statistical Package (SPSS) Version 16.0 From the calculation results with SPSS which is the variables of trust, security, service quality have a simultaneous and significant effect on purchasing decisions. While partially the variables of trust, security and service quality have a positive and significant effect on purchasing decisions. Keywords: Trust; Security; Service Quality; Buying decision